2021
DOI: 10.1186/s12957-020-02101-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, risk factors, and prognostic value of venous thromboembolism in ovarian cancer patients receiving chemotherapy: a systematic review and meta-analysis

Abstract: Background Venous thromboembolism (VTE) in ovarian cancer (OC) patients has been widely investigated, but our knowledge on the role of VTE in OC patients receiving chemotherapy is limited. The aim of our study was to investigate the prevalence, risk factors, and prognostic value of chemotherapy-associated VTE in OC. Methods Three databases (PubMed, Embase, and the Cochrane Library) were systematically searched from inception to October 14, 2020. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…ICU patients are considered to be at high risk for VTE even after routine prophylactic anticoagulant therapy (upper and lower extremity venous thrombosis, about 10%) [ 16 , 17 ]. In recent years, numerous studies have evaluated the risk factors related to VTE from the aspects of patient factors, tumor factors, and treatment factors [ 3 10 , 12 , 13 ], thus developing the thrombosis evaluation scale and model for outpatient and inpatient patients to predict the risk of thrombosis [ 14 , 15 ]. Recently, an ICU-VTE scale was created for ICU inpatients to assess the risk of thrombosis in critically ill patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICU patients are considered to be at high risk for VTE even after routine prophylactic anticoagulant therapy (upper and lower extremity venous thrombosis, about 10%) [ 16 , 17 ]. In recent years, numerous studies have evaluated the risk factors related to VTE from the aspects of patient factors, tumor factors, and treatment factors [ 3 10 , 12 , 13 ], thus developing the thrombosis evaluation scale and model for outpatient and inpatient patients to predict the risk of thrombosis [ 14 , 15 ]. Recently, an ICU-VTE scale was created for ICU inpatients to assess the risk of thrombosis in critically ill patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient factors that increase the risk of VTE include female sex, previous VTE history, advanced age, obesity, and ABO blood type [5][6][7][8]10].…”
Section: Patient Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that venous thromboembolism (VTE) is strongly associated with human cancer and orthopedic operations, [6,7] and the combination of these two factors may substantially increase the risk of VTE. [8] Moreover, VTE could lead to a poorer prognosis of tumor patients, [6,9] while some serum indices associated with clotting and thrombosis, such as platelet-to-lymphocyte ratio (PLR) and d-dimer showed good prognostic value in cancer patients. [10,11] However, the prognostic impact of VTE-related indices including platelet, fibrinogen, and d-dimer, has not been validated in osteosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Since Trousseau first described the relationship between cancer and thromboembolic disease in 1865, activation of the coagulation system via hosttumor interactions has been found in almost all types of cancer [11][12][13]. In addition, the tumorinduced hypercoagulation state is not simply an epiphenomenon but is also intrinsically involved in enhanced tumor growth, angiogenesis, metastasis, and the systemic inflammatory response [11,12,14].…”
Section: Introductionmentioning
confidence: 99%